Dynamic agricultural supply response under economic transformation: A case study of Henan province - Yu, Bingxin; Liu, Fengwei; You, Liangzhi (International Food Policy Research Institute, 2010)
China has experienced dramatic economic transformation and is facing the challenge of ensuring steady agricultural growth. This study examines the crop sector by estimating the supply response for major crops in Henan province from 1998 to 2007. We use a Nerlovian adjustment adaptive expectation model. The estimation uses dynamic Generalized Method of Moments (GMM) panel estimation based on pooled data across 108 counties. We estimate acreage and yield response functions and derive the supply response elasticities. This research links supply response to exogenous factors (weather, irrigation, government policy, capital investment, and infrastructure) and endogenous factors (prices). The significant feature of the model specification used in the study is that it addresses the endogeneity problem by capturing different responses to own- and cross-prices. Empirical results illustrate that there is still great potential to increase crop production through improvement of investment priorities and proper government policy. We confirm that farmers respond to price by both reallocating land and more intensively applying non-land inputs to boost yield. Investment in rural infrastructure, human capacity, and technology are highlighted as major drivers for yield increase. Policy incentives such as taxes and subsidies prove to be effective in encouraging grain production.